2023
DOI: 10.1038/s41598-023-37677-x
|View full text |Cite
|
Sign up to set email alerts
|

Viability of HepG2 and MCF-7 cells is not correlated with mitochondrial bioenergetics

Abstract: Alterations in metabolism are a hallmark of cancer. It is unclear if oxidative phosphorylation (OXPHOS) is necessary for tumour cell survival. In this study, we investigated the effects of severe hypoxia, site-specific inhibition of respiratory chain (RC) components, and uncouplers on necrotic and apoptotic markers in 2D-cultured HepG2 and MCF-7 tumour cells. Comparable respiratory complex activities were observed in both cell lines. However, HepG2 cells exhibited significantly higher oxygen consumption rates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Resazurin-based measurements of cell survival in the presence of SF-C n -TPP (Figure ) showed rather low toxicity of these compounds toward MRC5-SV40 cells at submicromolar concentrations that caused a marked decrease in mitochondrial membrane potential (Figure a). This result is consistent with recent findings indicating that cell viability could not be correlated with mitochondrial bioenergetics …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Resazurin-based measurements of cell survival in the presence of SF-C n -TPP (Figure ) showed rather low toxicity of these compounds toward MRC5-SV40 cells at submicromolar concentrations that caused a marked decrease in mitochondrial membrane potential (Figure a). This result is consistent with recent findings indicating that cell viability could not be correlated with mitochondrial bioenergetics …”
Section: Resultsmentioning
confidence: 96%
“…This result is consistent with recent findings indicating that cell viability could not be correlated with mitochondrial bioenergetics. 46 …”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the methods used to evaluate cell death in the present study may not have been as sensitive as those used in previous studies ( 45 , 48 ). Of note, the study by Doczi et al ( 63 ) demonstrated that the viability of HepG2 cells was not decreased by the complete inhibition of mitochondrial respiration. Nonetheless, in agreement with the study by Amorim et al ( 15 ), the FFA-treated HepG2 cells exhibited compensatory mitochondrial proliferation marked by the increased expression of the PPARGC1A gene and citrate synthase activity, secondary to excessive mitochondrial damage.…”
Section: Discussionmentioning
confidence: 98%
“…However, the deeper dispute is whether cancer cell survival actually depends on OXPHOS. Our recent contribution to this was to show that depending on the cancer cell culture type and targeted inhibition of respiratory components, OXPHOS can be demonstrated but could be dispensable for cell survival [ 12 ]. Therefore, we proposed that the association between OXPHOS and tumor viability likely relies on the particular cell type and the precise means of respiratory inhibition.…”
Section: Rationale For Complex I Targeting In Cancermentioning
confidence: 99%